Idiopathic Juxtafoveolar Telangiectasis Type 1A. A Case Report - Pandey, A; Anand, A; Singh, A; Chandra, A (Journal of Universal College of Medical Sciences, 2014)
No Abstract Available Idiopathic juxtafoveolar telangiectasisis a descriptive term for various disease entities presenting with incompetence, ectasia, and/or irregular dilations of the capillary network affecting only the juxtafoveolar region of one or both eyes. A 65 years male presented with the chief complaint of painless progressive diminution of vision in his left eye for 6 months’ duration. Past ocular, surgical, medical, drug and family history was non contributory. The patient was non hypertensive and non diabetic. His best corrected visual acuity was 6/60 right eye and 6/36 left eye. Right eye, fundus was grossly normal whereas, on the left eye, few microaneurysms and circinate pattern of hard exudates were noticed on the perifoveolar region. Fundal reflex was dull and the foveal depression was absent indicating thickening. Fluorescein angiography showed clusters of telangiectatic vessels around exudates, hyperfluorescent dots of microaneurysms with a circinate pattern of leakage in the late phase. Optical coherence tomography showed macular thickening of 487 micrometer with cystoid changes. Injection Bevacizumab 0.2ml was given after final diagnosis of Left Eye Idiopathic Juxtafoveolar Telangiectasis Type 1A. Three types of idiopathic juxtafoveolar telangiectasis has been defined. Its pathophysiology is also less understood and the treatment modalities are not established yet.This case was an incidental finding, as these patients do not oftenly have profound diminution of vision, unless neovascularization has occurred and the clinical features too are very subtle. DOI: http://dx.doi.org/10.3126/jucms.v2i3.11827 Journal of Universal College of Medical Sciences Vol.2(3) 2014: 38-40